PERBEDAAN GENDER MENGENAI PERCEIVED RISK PADA PEMBELIAN ONLINE - Marianty, Dwi (KINERJA, 2015)
This study aimed to examine the difference in perceived risk between Men and Women in the buying and selling online. Dimensions are used to in this research is financial risk, psychological risk, time risk, privacy risk, fraud risk, product risk, information risk and delivery risk. From these results  perceived risk that there are differences between men and women (in the books online purchases). Women respondents have an average value higher than the Men Women respondents feel that means a higher risk than men. Keyword: Financial risk, psychological risk, time risk, privacy risk, fraud risk, product risk, information risk and delivery risk